2004
DOI: 10.1353/dem.2004.0023
|View full text |Cite
|
Sign up to set email alerts
|

Housing and wealth inequality: Racial-ethnic differences in home equity in the United States

Abstract: In our study, we took a first step toward broadening our understanding of the sources of both housing and wealth inequality by studying differences in housing equity among blacks, Hispanics, Asians, and non-Hispanic whites in the United States. Using data from the American Housing Survey, we found substantial and significant gaps in housing equity for blacks and Hispanics (but not for Asians) compared with whites, even after we controlled for a wide range of locational, life-cycle, socioeconomic, family, immig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
176
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(206 citation statements)
references
References 49 publications
6
176
1
Order By: Relevance
“…On average, we find that neighborhoods with more African Americans pay a smaller percentage of their income in property taxes as compared to neighborhoods with more Caucasians. Studies have suggested that housing values and appreciation is lower in African American communities (Brown, 2012;Krivo and Kaufman, 2004). This may help explain why assessments and property tax burdens of African Americans are less, too.…”
Section: Emprical Resultsmentioning
confidence: 99%
“…On average, we find that neighborhoods with more African Americans pay a smaller percentage of their income in property taxes as compared to neighborhoods with more Caucasians. Studies have suggested that housing values and appreciation is lower in African American communities (Brown, 2012;Krivo and Kaufman, 2004). This may help explain why assessments and property tax burdens of African Americans are less, too.…”
Section: Emprical Resultsmentioning
confidence: 99%
“…Barriers to securing affordable housing severely hinder ethnic minorities' access to homeownership, leading to increasing wealth inequality (Krivo and Kaufman 2004;Oliver and Shapiro 1995).…”
Section: Ethnic Clustering: Chosen or Constrained?mentioning
confidence: 99%
“…The authors argued that this result might be due to the possibility that Asian American households tend to view their home as an investment. Coulson (1999), Painter, Gabriel andMyers (2001), and Krivo and Kaufman (2004) compared home ownership rates between Asian Americans and other ethnic groups. Their findings consistently showed that Asian Americans were less likely than their white counterparts to own a home.…”
Section: Housing Issuesmentioning
confidence: 99%